Genetic variability and association of characters in the 1995 RRIM Hevea germplasm core collection for yield improvement - Adifaiz, A. F.; Maiden, N. A.; Nusaibah, S. A.; Sulaiman, Z.; Rafii, M. Y. (Springer Science and Business Media LLC, 2021)
Genetic improvement of the rubber tree (Hevea brasiliensis) through conventional breeding approaches depends mainly on the availability of diverse germplasm and the amount of genetic variability present in the population. The present study was undertaken to evaluate the extent of genetic variability in the 1995 Rubber Research Institute of Malaysia (RRIM) Hevea germplasm core collection to determine the correlation and the direct and indirect effects of morphological and bark structural characters on latex yield. The analysis of variance showed highly significant differences among the genotypes for all the nine characters studied. The phenotypic coefficient of variations was higher than the genotypic coefficient of variations for all characters studied, suggesting that the apparent variation is not only genetic but also influenced by the growing environment in the expression of the traits. High heritability and high genetic advance were noted for latex yield, indicating the possibility of improvement for this character through phenotypic selection. Latex yield showed significant and positive correlations with plant girth, total number of latex vessel rings, total bark thickness, and total leaf area at both phenotypic and genotypic level. Path coefficient analysis revealed the highest direct effect of plant girth on latex yield, followed by total number of latex vessel rings and total bark thickness indicating the importance of these characters for yield improvement and their potential as reliable indicators for indirect selection in the established core collection.